Mekanisme Kendali Hibrida Berbasis Internet of Things untuk Mitigasi Kekeruhan pada Kolam Lele (Clarias gariepinus) secara Intensif - Aldyan Eka Permana; Muchamad Malik; Wardatul Jannah (CV. IRA PUBLISHING, 2026)
Intensification of catfish farming at high stocking density is often constrained by drastic water-quality degradation, including increased turbidity, which can trigger stress and mass mortality in commodities. This study aims to design and build an Internet of Things-based automatic catfish pond water turbidity control system to maintain water parameter stability according to quality standards in real-time. The research method applied is Research and Development, which includes microcontroller-based hardware design, optical turbidity sensor integration, and web-based monitoring interface development. The system uses an on-off control algorithm with a hysteresis technique to intelligently regulate the circulation pump's activation at a danger threshold of 50 Nephelometric Turbidity Units and a safe limit of 25 Nephelometric Turbidity Units. The main findings indicate that the system has a very fast dynamic response, with a sensor delay of less than 2 seconds. In maximum disturbance load testing, the device successfully restored water clarity in an average time of 165 seconds without actuator oscillation. This study concludes that integrating automatic control technology and remote monitoring effectively improves water quality management efficiency and mitigates the risk of harvest failure for farmers.